An improved edge recombination algorithm for scheduling problems of drone package delivery. (17th February 2018) - Chen, Meng-Hui; Lan, Yan-Qi; Hu, Jun; Xu, Zhi
Abstract: The package delivery industry has become one of the more prominent industries worldwide, one which is indispensable to many people's daily lives. Clients expect their packages to be delivered as promptly as possible, and to this end, leading delivery agencies like Amazon and DHL have begun to use drones for package delivery. Drones are aircraft or flying machines either controlled by trained pilots or which autonomously follow a pre-programmed route. However, companies using drones for deliveries have experienced several problems. In particular, package delivery time and tardiness must be minimized. This paper therefore focuses of the problem of minimizing delivery time and tardiness, proposing a Hybrid block-based edge recombination algorithm (HBERA) to solve the package delivery problem. The performance results of the proposed algorithm were compared with those of the edge recombination algorithm (ERX), showing that the proposed methodology's computational result showed a clearly optimal group of solutions. In addition, HBERA also can be proved to be able to solve the multiple-objective problems.